Prevalence and subtype distribution of Blastocystis sp. infecting children from a rural community in Panama. (May 2020) - Perea, M.; Vásquez, V.; Pineda, V.; Samudio, F.; Calzada, J.E.; Saldaña, A.
Abstract: Blastocystis sp. is a commonly reported intestinal parasite with a worldwide distribution. Phylogenetic analyses describe at least 17 subtypes for this parasite, and nine of them have been found in humans. However, the prevalence and some epidemiological characteristics of this parasitic infection in rural communities are not well known. The objective of this cross-sectional study was to evaluate the prevalence, subtypes, and epidemiological factors related to Blastocystis sp. Infection in children from of a small rural community in the central area of Panama. For this, 66 fecal samples from children (1 to 12 years old), were initially analyzed for the presence of parasites by a formalin-ethyl acetate/concentration method. Molecular detection and identification of Blastocystis sp. subtypes were carried out by amplification and sequencing of a partial fragment of the small-subunit ribosomal RNA gene. Using data from a questionnaire, analyses of epidemiological conditions potentially associated with Blastocystis sp. transmission were also conducted. Microscopic diagnostics showed that 33.3% (22/66) of the analyzed samples presented entero-parasites. Among them, Blastocystis sp. was the most prevalent, with 21.2% (14/66), followed by the E. histolytica/dispar/moshkovskii complex 4.5% (3/66), Giardia lamblia 1.5% (1/66) and Strongyloides stercoralis 1.5% (1/66). PCR-based analyses detected a prevalence of Blastocystis sp. infection of 74.2% (49/66) in apparently healthy children. Phylogenetic analysis revealed two different subtypes of this parasite: ST1 with 42.2% (28/66) infected, and ST3 with 31.8% (21/66) infected. In addition, recent diarrhea was significantly associated with Blastocystis sp. infection. None of the other risk factors evaluated was statistically associated with infection. These results highlight the need to further investigate clinical, epidemiological, and genetic characteristics of Blastocystis sp. infections in this community. Highlights: Infection with Blastocystis sp. is very frequent among children from a rural community in Panama ST1 and ST3 subtypes were found with a slight predominance of ST1 Statistical analysis showed that recent diarrhea in children was significantly related to Blastocytis sp. infection Additional clinical and epidemiological studies related to blastocystosis in this community are needed